Identifikasi Beberapa Aksesi Jarak Pagar (Jatropha curcas L.) Melalui Analisis RAPD dan Morfologi - Susanti Diana; Andi Wijaya; Benyamin Lakitan; Memen Surahman (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2009)
The objective of this research was to study and cluster of Jatropha germplasm belonging to University of Sriwijaya. This research was conducted from September 2007 until July 2008. The research used 14 accessions of Jatropha taken from some regions in Indonesia, namely: Komering, Palembang, Yogyakarta, Indralaya, ATP2, Pontianak, Lahat, Pagaralam, Curup, Lampung, Medan Aceh Besar, Pidi and Gorontalo. Accessions of Jatropha curcas L. were planted at Agro Techno Park (ATP) Bakung village, Indralaya Utara district Ogan Ilir, South Sumatera using Randomized Complete Block Design. RAPD analysis using 20 primers was done at RGCI (Research Group on Crop Improvement), Bogor Agricultural University. Dendrogram based on RAPD analysis produced five groups that were: the first group was Komering, Lahat, Pidi, Indralaya, Aceh Besar, Pontianak and Curup. The second group was Palembang and ATP2. The third group was Pagaralam, Gorontalo, and Medan. Lampung was included in to fourth group. The fifth group was Yogyakarta. Dendrogram from morphological marker had also five groups. First group was: Komering, Indralaya, Pontianak. Lahat, and Pagaralam. Second group was: Palembang, Lampung, Pidi, Medan, and ATP2. Third group was: Curup. Fourth group was: Yogyakarta and Gorontalo. Fifth group was: Aceh Besar. The difference of member from each groups between dendrogram using RAPD and morphological markers indicated that the bands resulted from RAPD did not have relation with characters observed. Key words: Jatropha curcas L, RAPD analysis, Morphologycal marker, cluster analysis